POLIOMYELITIS, VACCINES AND POSSIBLE COMPLETE ERADICATION - BOBBO. K. A; USMAN M.A (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
Poliomyelitis commonly known as polio is one of the early 18th to 20th centuries most feared, most deadly and wide spread epidemic disease. Studies have shown that it results from infection by 3 serotypes of poliovirus leading to spectrum of clinical manifestation imprecise infection, nonspecific febrile illness, meningitis, paralysis and even death. For over a century, combating efforts were made by researchers to develop a vaccine to contain spread of the viral causing disease which lead to the development of an inactivated (or "killed") polio vaccine (IPV) and oral (or "live") PV vaccine (OPV) as far back between the early 1950 to mid-1960. These 2 vaccines were developed towards preventing poliomyelitis and so far, have been officially recorded with singular dropping leading to eradication of this condition in most part of the world. Yet this disease condition remains endemic in countries like: Afghanistan, India, Nigeria and Pakistan. It has been reported in 2014 that as of 2012, more than 50% of the world’s present cases occurred in Nigeria. This posted a belief that the key to complete eradication of poliomyelitis is in Nigeria. This might be due to high refusal by controversies claims based on “unfounded rumours” probable due to lack of in-depth knowledge of the disease and vaccine. Nigeria might be holding the key into total elimination, huge amount of money invested to identify most of the set back. Drawing a final entry strategy by findings base on a case study, issues that need to be tackled and recommendations for a complete eradication in Nigeria and the globe at large. This should include enlightenment of history behind the disease and a study into the “unfounded rumours”.